Palestine Is Throwing a Party and the Whole World Is Invited : Capital and State Building in the West Bank - Rabie, Kareem, 1980- (Book collections on Project MUSE., 2021)
"Kareem Rabie examines how Palestine's desire to fully integrate its economy into global markets through large-scale investment projects represented a shift away from political state building with the hope that a thriving economy would lead to a free and functioning Palestinian state."--